2021
DOI: 10.1038/s41598-021-97153-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the signal cross talk via CCL26 in the tumor microenvironment in osteosarcoma

Abstract: Interaction with surrounding healthy cells plays a major role in the growth and metastasis of osteosarcoma. In this study, we hypothesized that humoral factors, which do not require direct contact with cells, are involved in the interaction between osteosarcoma and the surrounding cells. We identified the humoral factor involved in the association between tumor cells and surrounding normal cells using a co-culture model and investigated the significance of our findings. When human osteosarcoma cells (MG63) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…(9) Conversely, CCL8, CXCL1, and CCL26-all significantly higher in Black patients in the present study-promote tumorigenesis and cancer progression in various malignancies. (10)(11)(12) Results from the analysis of immune cell populations appear to correlate with our cytokine findings. We observed higher levels of nonclassical monocytes and NKT-like cells in Black patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…(9) Conversely, CCL8, CXCL1, and CCL26-all significantly higher in Black patients in the present study-promote tumorigenesis and cancer progression in various malignancies. (10)(11)(12) Results from the analysis of immune cell populations appear to correlate with our cytokine findings. We observed higher levels of nonclassical monocytes and NKT-like cells in Black patients.…”
Section: Discussionsupporting
confidence: 74%
“…(9) Conversely, CCL8, CXCL1, and CCL26—all significantly higher in Black patients in the present study—promote tumorigenesis and cancer progression in various malignancies. (10-12)…”
Section: Discussionmentioning
confidence: 99%
“…Eotaxin-3 (CCL26), IL-9, TSLP, and Fas were differentially expressed (DE) on surfaces with Ra = 1.5 µm. These factors are responsible for the stimulation of immune cells to sites of inflammation ( Goswami and Kaplan, 2011 ; Kawano et al, 2021 ) and immune cell death ( Volpe et al, 2016 ), and cancer has been associated with immune privilege and increased invasiveness and metastasis ( Abrahams et al, 2003 ; Lan et al, 2018 ; Das et al, 2021 ). Likewise, MDA-MB-231 cells cultured on surfaces with Ra = 1.5 µm showed enriched bioprocesses for inflammation ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, they also showed an increased number of lung metastases in a lung metastasis model in nude mice in which recombinant CCL26 was added. 25 Another study demonstrated that CCL26 induces tumor-associated macrophage infiltration by binding to the CCL26 receptor in colorectal cancer. 26 Furthermore, hypoxia is a common feature of solid tumors, and CCL26 can be activated by hypoxia-inducible factors.…”
Section: Discussionmentioning
confidence: 99%